Why Argentine Private Universities Continue to Lag - Rabossi, Marcelo (International Higher Education, 2012)
Private higher education accounts for half of total enrollment in Latin America but only a fifth in Argentina. For reasons including statist norms, tough regulation, and public university stature, it has been difficult for Argentina's private higher education to attain the position held by its counterparts in the region. Whether that may now change is unclear.